Revisiting trypanosomatid nucleoside diphosphate kinases - Miranda, Mariana Reneé (2021)
Background: An increasing amount of research has led to the positioning of nucleoside diphosphate kinases (NDPK/NDK) as key metabolic enzymes among all organisms. They contribute to the maintenance the intracellular di- and tri- phosphate nucleoside homeostasis, but they also are involved in widely diverse processes such as gene regulation, apoptosis, signal transduction and many other regulatory roles. Objetive: Examine in depth the NDPKs of trypanosomatid parasites responsible for devastating human diseases (e.g., Trypanosoma cruzi, Trypanosoma brucei and Leishmania spp.) which deserve special attention. Methods: The earliest and latest advances in the topic were explored, focusing on trypanosomatid NDPK features, multifunctionality and suitability as molecular drug targets. Findings: Trypanosomatid NDPKs appear to play functions different from their host counterparts. Evidences indicate that they would perform key roles in the parasite metabolism such as nucleotide homeostasis, drug resistance, DNA damage responses and gene regulation, as well as host-parasite interactions, infection, virulence and immune evasion, placing them as attractive pharmacological targets. Main conclusions: NDPKs are very interesting multifunctional enzymes. In the present review, the potential of trypanosomatid NDPKs was highlighted, raising awareness of their value not only with respect to parasite biology but also as molecular targets.